HUBUNGAN ANTARA MATRIX METALLOPROTEINASE-13 DAN TISSUE INHIBITOR METALLOPROTEINASE-1 PADA PASIEN PERIODONTITIS KRONIS - Maulidatul Husna; Nasution aini hariyani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction:  Chronic periodontitis is a multifactorial disease that causes rapid destruction of the tissues supporting the teeth and that may lead to tooth loss. Matrix metalloproteinase-13 (MMP‐13) levels have been higher in the gingival crevicular fluid of chronic periodontitis patients and tissue inhibitor of metalloproteinase-1 (TIMP‐1) is an endogenous inhibitor of MMPs implicated in inflammation.  This review purpose to discuss the relationship between matrix metalloproteinase-13 and tissue inhibitor of metalloproteinase-1 in chronic periodontitis. Review: The level of MMP-13 plays a role in the pathogenesis of chronic periodontitis. MMP-13 (collagenase-3) is the third member of the collagenase subfamily of MMPs and it is a potent gelatinolytic and collagenolytic enzyme expressed by different cell types. The activity of these MMPs is primarily controlled by tissue inhibitors, known as TIMPs, which have an N-terminal domain that is able to inhibit MMPs. Some studies showed that MMP-13 is associated with soft and hard tissue damage during the progression of chronic periodontitis. The balance between MMPs and TIMPs plays an important role in the degradation of the extracellular matrix. In healthy periodontal conditions, TIMP levels are generally higher than in unhealthy conditions, in which MMP levels exceed the level of TIMP. Conclusion: Chronic periodontitis is characterized by the increase of MMP-13 expression during the progression of the disease, the active sites show a decrease of TIMP-1 levels in association with the elevation of MMP-13.